The Experience of Taking Control over the Illegal Turnover of the Sturgeon Fishes, Committed by Forms of Organized Crime, Applied Abroad - AMANGELDIYEV, Darkhan Amangeldievich (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
The presented article takes a look at the problems of resisting the illegal turnover of the sturgeon fishes, committed by forms of organized crime. At present, when the moratorium on fishing the sturgeon species in the Caspian has been adopted, poaching continues to be the only source of the illegal turnover of the products, made from the sturgeon fishes, and at the same time, it is the major threat to the sturgeon populations, and the poaching takes organized forms. The author considers the causes and circumstances that lead to the emergence of organized forms and committing illegal fishing of the sturgeon fishes in the Ural River and the part of the Caspian that belongs to Kazakhstan, and why the illegal turnover of sturgeon flesh and roe persists. Among the main causes of the illegal turnover and poaching, the author names the unemployment problems of the local population, the high demand on the products made from the sturgeon fishes abroad, the insufficient government control over the issue. The experience of implementing some organizational and law-enforcement measures has been examined, that are applied in different states, in order to prevent the poaching violations, as regards the sturgeon fishes and the illegal turnover of the sturgeon products. As the directions of improving the legal basis, introducing harsher criminal responsibility for poaching is suggested, and a set of organizational measures for putting an end to the illegal turnover of the products from the sturgeon fishes.
Keywords: the sturgeon fishes, roe, caviar, organized crime, poaching, the illegal turnover